Russia’s Asia pivot: engaging the Russian Far East, China and Southeast Asia - Dave, Bhavna (2016)
The Russia-ASEAN summit being held in Sochi on 19-20 May 2016 to mark twenty years of Russia’s dialogue partnership with ASEAN is a further indicator of President Vladimir Putin’s ‘pivot to Asia’ policy, triggered also by its current confrontation with the west. Through this pivot, Moscow wants to assert Russia’s geopolitical status as a Euro-Pacific as well as AsiaPacific power. It is a pragmatic response to the shifting of global power to Asia. It also builds on the growing Russo-Chinese relations to develop the Russian Far East, a resource-rich but underdeveloped region into the gateway for expansion of Russia into the Asia Pacific. At the same time, the growing asymmetry in achieving the economic and strategic goals of Russia and China has resulted in fears that the Russian Far East will turn into a raw materials appendage of China. Moscow lacks the financial resources to support Putin’s Asia pivot. Therefore, Russia needs to strengthen ties with other Asia-Pacific countries and ASEAN as a regional grouping so as to attract more diversified trade and investments into its Far East region. It is in this context that the Sochi summit takes on added significance. However, given Russia’s sporadic interest in Southeast Asia and its strategic role defined mainly by the limited potential of Russian energy and arms exports to ASEAN Member States, the PR diplomacy and summitry at Sochi may not deliver substantive outcomes for Russia. Nonetheless, Moscow aims to enhance its status in the east and seek business and strategic opportunities through the summit thereby compensating to some extent Russia’s loss following the sanctions imposed by the west over the annexation of Crimea.